Penerapan Metode Per Connection Classifier dan Failover Untuk Meningkatkan Optimasi Koneksi Jaringan Internet - Aris Aditya Nugraha; Arif Harbani (Universitas Binaniaga Indonesia, 2023)
The need for internet access is currently very high considering the need to search for information, articles or the latest knowledge. Many agencies or companies have integrated the internet network into their main needs in carrying out a goal in order to achieve the vision or mission of the agency or company that must be completed in accordance with the business processes that have been made. Basically, all companies want an internet connection that is effective and efficient in its use. Therefore, a solution arises from the existing problem to use two Internet Service Providers and make the proxy router a Load Balancer. The mechanism is that the proxy balances the load on an existing network. Based on the system development method used, namely the Network Development Life Cycle (NDLC), before determining the load balancing method used, an analysis of the traffic conditions running on a network is carried out and monitoring to obtain history on a network. The selection of Per Connection Classifier Load Balancing can meet the criteria because it optimizes existing connections so that there is no buildup or overload. Application of the Failover Technique, that is, if one connection from the ISP is lost, it will automatically look for a gateway that is used as a backup so that it can back up all network traffic. In addition to Load Balancing and Failover, bandwidth management is also implemented according to the needs and characteristics of user usage. In the results obtained from the evaluation for the Network Expert Test, there are results with a feasibility presentation of 100%, which means it is categorized as